Pengembangan Media Moodboard Pada Mata Pelajaran Desain Busana Untuk Siswa Kelas Xi Smk Negeri 1 Seririt - Luh Maharani Tanaya; Putu Agus Mayuni; Made Diah Angendari (Jurnal BOSAPARIS: Pendidikan Kesejahteraan Keluarga, 2022)
Penelitian ini dilakukan dengan tujuan untuk mengkaji dan menganalisis terkait proses Pengembangan serta menguji kelayakan media Moodboard pada mata pelajaran Desain Busana untuk siswa kelas XI di SMK Negeri 1 Seririt. Penelitian ini merupakan jenis Penelitian dan Pengembangan (Research and Development atau R & D). Pengembangan produk ini menggunakan model ADDIE yang terdiri dari: (analysis, design, development, implementation, and evaluation). Angket digunakan sebagai lembar penilaian produk. Hasil penilaian pada uji ahli materi dalam penelitian ini mendapat presentase sebanyak 97% sehingga produk dikatakan “sangat baik” dan tidak perlu direvisi. Hasil penilaian pada uji ahli media dalam penelitian ini berada pada rerata presentasi 88% sehingga produk berupa media moodboard dikatakan “baik” dan tidak perlu direvisi. Pada tahap terakhir yakni implementasi, tahap ini produk di uji cobakan kepada 6 orang siswa dan mendapatkan hasil rerata presentase sebanyak 90% sehingga media moodboard mendapat kualifikasi “sangat baik”. This research was conducted with the aim of reviewing and anaIyzing reIated to the deveIopment process and testing the feasibiIity of Moodboard media on the subject of Fashion Design for XI grade students at SMK Negeri 1 Seririt. Moodboard is a media that can be used to heIp probIems in fashion design, moodboard contains a coIIection of images arranged in various interesting forms. Moodboard media research is a type of Research and DeveIopment (R & D). The deveIopment of this Iearning media product uses the ADDIE modeI which consists of: (anaIysis, design, deveIopment, impIementation, and evaIuation). The questionnaire is used as a product assessment sheet. The resuIts of the assessment on the materiaI expert test in this study received a 97% so that the product was said to be "very good" and did not need to be revised. The resuIts of the assessment on the media expert test in this study receiced an average percentage of 88% so the moodboard media was said to be "good" and did not need to be revised. In the impIementation stage, at the product was tested on 6 students and got an average percentage of 90% so that the moodboard media got "very good" quaIifications. This research was conducted with the aim of reviewing and anaIyzing reIated to the deveIopment process and testing the feasibiIity of Moodboard media on the subject of Fashion Design for XI grade students at SMK Negeri 1 Seririt. Moodboard is a media that can be used to heIp probIems in fashion design, moodboard contains a coIIection of images arranged in various interesting forms. Moodboard media research is a type of Research and DeveIopment (R & D). The deveIopment of this Iearning media product uses the ADDIE modeI which consists of: (anaIysis, design, deveIopment, impIementation, and evaIuation). The questionnaire is used as a product assessment sheet. The resuIts of the assessment on the materiaI expert test in this study received a 97% so that the product was said to be "very good" and did not need to be revised. The resuIts of the assessment on the media expert test in this study receiced an average percentage of 88% so the moodboard media was said to be "good" and did not need to be revised. In the impIementation stage, at the product was tested on 6 students and got an average percentage of 90% so that the moodboard media got "very good" quaIifications.